Artery of Percheron Infarction: A Case Report of Bilateral Thalamic Stroke Presenting with Acute Encephalopathy - Charles Donohoe; Nooshin Kiani Nia; Patricia Carey; Vamsi Vemulapalli (Case Reports in Neurological Medicine)
The artery of Percheron (AOP) is a relatively rare anatomic variant in which a solitary arterial trunk branches from the proximal segment of the posterior cerebral artery and provides arterial supply to the paramedian region of the thalami bilaterally and often to the rostral part of the midbrain. Occlusion of the artery of Percheron results in bilateral paramedian thalamic infarcts with and without midbrain involvement. Recognition of this condition as an acute stroke may be challenging due to various nonlocalized clinical presentations, given the wide range of neurological functions subserved by the thalamus. Prompt neuroimaging, preferably with magnetic resonance imaging (MRI), in conjunction with familiarity with this relatively rare vascular variation can facilitate initiation of appropriate time contingent thrombolytic treatment and improved long-term prognosis. We present a case of a 56-year-old African American female with a bilateral thalamic infarct secondary to the artery of Percheron thromboembolism. This patient presented unresponsive without focal neurologic findings but with an initial Glasgow Coma Score (GCS) of 7, and subsequent computed tomographic (CT) head revealed bilateral thalamic hypodensities. Confirmatory MRI exhibited bilateral subacute thalamic infarcts, which were thought to be embolic with the source from the left ventricular thrombus as the patient had at least three distinct clots. Unfortunately, the patient’s mental status did not improve significantly, and she was discharged to a nursing facility for extended care. AOP infarction may be missed on vascular imaging utilizing CT, MRI, and even catheter angiography. Clinical recognition that the AOP is one of the only single artery occlusions that can affect bilateral structures and frequently present solely as altered mental status without focal neurologic deficits is crucial to the diagnosis.